Induction and evaluation of triploidy in edible oyster, Crassostrea madrasensis (Preston) - an approach to enhance bivalve aquaculture - Mallia, Jyoti V; Thomas, P C; Muthiah, P (Indian Journal of Fisheries, 2011)
Induced triploidy can be used for enhancing production of commercially valuable bivalve species. Triploid individuals, having an extra set of chromosomes (3n) typically exhibit reduced gametogenic activity leading to better growth since the energy used for reproduction is reallocated for somatic growth. In India, research on genetic manipulation of the edible oyster, Crassostrea madrasensis by triploidy inducement and assessment of triploid performance as a strategy to increase production has been underway since 1998. This article outlines the potential of using triploidy in bivalve culture for better returns